The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Metrics of progress in the understanding and management of threats to Australian birds - S. T. Garnett; S. H. M. Butchart; G. B. Baker; E. Bayraktarov; K. L. Buchanan; A. A. Burbidge; A. L. M. Chauvenet; L. Christidis; G. Ehmke; M. Grace; D. G. Hoccom; S. M. Legge; et al. (Conservation Biology, 2019)
Although evidence‐based approaches have become commonplace for determining the success of conservation measures for the management of threatened taxa, there are no standard metrics for assessing progress in research or management. We developed 5 metrics to meet this need for threatened taxa and to quantify the need for further action and effective alleviation of threats. These metrics (research need, research achievement, management need, management achievement, and percent threat reduction) can be aggregated to examine trends for an individual taxon or for threats across multiple taxa. We tested the utility of these metrics by applying them to Australian threatened birds, which appears to be the first time that progress in research and management of threats has been assessed for all threatened taxa in a faunal group at a continental scale. Some research has been conducted on nearly three‐quarters of known threats to taxa, and there is a clear understanding of how to alleviate nearly half of the threats with the highest impact. Some management has been attempted on nearly half the threats. Management outcomes ranged from successful trials to complete mitigation of the threat, including for one‐third of high‐impact threats. Progress in both research and management tended to be greater for taxa that were monitored or occurred on oceanic islands. Predation by cats had the highest potential threat score. However, there has been some success reducing the impact of cat predation, so climate change (particularly drought), now poses the greatest threat to Australian threatened birds. Our results demonstrate the potential for the proposed metrics to encapsulate the major trends in research and management of both threats and threatened taxa and provide a basis for international comparisons of evidence‐based conservation science.

Analysis of factors implicated in the recent decline of Australia's mammal fauna - N. L. McKenzie; A. A. Burbidge; A. Baynes; R. N. Brereton; C. R. Dickman; G. Gordon; L. A. Gibson; P. W. Menkhorst; A. C. Robinson; M. R. Williams; J. C. Z. Woinarski (Journal of Biogeography, 2007)
Aim To assess whether eight factors thought to be involved in the extinction process can explain the pattern of recent decline in Australia's mammal fauna. Location Australia. Methods We compiled the first comprehensive lists of mammal species extant at the time of European settlement in each of Australia's 76 mainland regions, and assigned a current conservation status to each species in each region to derive an index of faunal attrition. We then sought to explain the observed region‐to‐region variation in attrition (the dependent variable) by building a series of models using variables representing the eight factors. Results A strong geographically based pattern of attrition emerged, with faunal losses being greatest in arid regions and least in areas of high rainfall. The Akaike information criterion showed support for one model that explained 93% of the region‐to‐region variation in attrition. Its six variables all made independent contributions towards explaining the observed variation. Two were environmental variables, namely mean annual rainfall (a surrogate for regional productivity) and environmental change (a measure of post‐European disturbance). The other four were faunal variables, namely phylogenetic similarity, body‐weight distribution, area (as a surrogate for extent of occurrence), and proportion of species that usually shelter on the ground (rather than in rock piles, burrows or trees). Main conclusions In combination with historical evidence, the analysis provides an explicit basis for setting priorities among regions and species. It also shows that the long‐term recovery of populations of many species of Australian mammals will require introduced predator suppression as well as extensive habitat management that includes controlling feral herbivores. Specifically, habitat management should restore aspects of productivity relevant to the types of species at risk and ensure the continual availability of suitable refuges from physiological stressors.

Accounting for Management Costs in Sensitivity Analyses of Matrix Population Models - PETER W.J. BAXTER; MICHAEL A. McCARTHY; HUGH P. POSSINGHAM; PETER W. MENKHORST; NATASHA McLEAN (Conservation Biology, 2006)
Traditional sensitivity and elasticity analyses of matrix population models have been used to inform management decisions, but they ignore the economic costs of manipulating vital rates. For example, the growth rate of a population is often most sensitive to changes in adult survival rate, but this does not mean that increasing that rate is the best option for managing the population because it may be much more expensive than other options. To explore how managers should optimize their manipulation of vital rates, we incorporated the cost of changing those rates into matrix population models. We derived analytic expressions for locations in parameter space where managers should shift between management of fecundity and survival, for the balance between fecundity and survival management at those boundaries, and for the allocation of management resources to sustain that optimal balance. For simple matrices, the optimal budget allocation can often be expressed as simple functions of vital rates and the relative costs of changing them. We applied our method to management of the Helmeted Honeyeater ( Lichenostomus melanops cassidix ; an endangered Australian bird) and the koala ( Phascolarctos cinereus ) as examples. Our method showed that cost‐efficient management of the Helmeted Honeyeater should focus on increasing fecundity via nest protection, whereas optimal koala management should focus on manipulating both fecundity and survival simultaneously. These findings are contrary to the cost‐negligent recommendations of elasticity analysis, which would suggest focusing on managing survival in both cases. A further investigation of Helmeted Honeyeater management options, based on an individual‐based model incorporating density dependence, spatial structure, and environmental stochasticity, confirmed that fecundity management was the most cost‐effective strategy. Our results demonstrate that decisions that ignore economic factors will reduce management efficiency.